ADAPTIVE GOVERNANCE IN POVERTY ALLEVIATION EFFORTS THROUGH ECOTOURISM AT NGERONG CAVE IN RENGEL VILLAGE - Octavia Ranja Riskulloh; Faridatul Istighfaroh; Ida Swasanti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study discusses poverty alleviation efforts through ecotourism in Rengel Village, Rengel District, Tuban Regency. This study aims to analyse the application of adaptive governance in poverty alleviation efforts through Ngerong Cave Ecotourism in Rengel Village. This research method used a descriptive qualitative approach and data were collected through observation, interviews, and documentation. Based on the adaptive governance theory from Sharma-Wallace (2018), the study results lie on the eight indicator: collaboration, coordination, social capital development, community empowerment and involvement, capacity building, connecting knowledge and decision-making through data collection, improving leadership capacity, and utilizing or creating governance opportunities. The findings reveal that efforts to alleviate poverty through Ngerong Cave Ecotourism have not shown significant improvement in poverty caused by lack of collaboration among various parties, the lack of community empowerment and involvement, and the absence of proactive measures to create governance opportunities. On the other hand, managers have coordinated professionally, built substantial social capital, increased capacity, and made decisions in accordance with the adaptive governance approach. This study contributes to expanding the literature on adaptive governance used in rural ecotourism as an effort to reduce poverty.